2015
DOI: 10.1007/s13277-015-3798-z
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid morpholine amide (RAMA) inhibits expression of Fas ligand through EP1 receptor in colon cancer cells

Abstract: Among the members of tumour necrosis factor family Fas ligand on binding to its receptor strongly induces apoptosis of tumour-infiltrating lymphocytes (TIL). Thus, FasL acts as an inhibitor of anti-tumour immune response. The present study demonstrates that retinoic acid morpholine amide (RAMA) significantly suppresses FasL expression in colon cancer cells in a dose- and time-dependent manner. The suppression of FasL mRNA and proteins was significant at a concentration of 30 μM after 48 h in CLT85 and HT26 col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Morpholine and its derivatives are used as solvents, corrosion inhibitors, rubber additives, antioxidants, as well as in the production of drugs and herbicides. Morpholine derivatives are also of interest as they show biological activities such as anti-inflammatory, analgesic, antidepressant, and antitumor (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Morpholine and its derivatives are used as solvents, corrosion inhibitors, rubber additives, antioxidants, as well as in the production of drugs and herbicides. Morpholine derivatives are also of interest as they show biological activities such as anti-inflammatory, analgesic, antidepressant, and antitumor (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…EGFR phosphorylation and cell invasiveness induced by PGE 2 were blocked after EP 1 receptor knockdown by siRNA, or by the EP 1 receptor antagonist ONO-8711 [12]. Pharmacological and genetic studies show the selective EP 1 inhibitor significantly reduced colon cancer development, indicating this receptor plays a role in colon carcinogenesis [13]. A research showed that long-term administration of ONO-8711 in rat diet reduced azoxymethane-induced colon cancer incidence, multiplicity and volume of colon carcinomas [14].…”
Section: Introductionmentioning
confidence: 99%